IMPLEMENTASI SAK ETAP PADA TAMAN REKREASI KELUARGA KEMBENGAN SARI - Ni Made Rukmiyati (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Micro, small and medium enterprises (MSMEs) make a major contribution to the Indonesian economy and are the main drivers. MSMEs need financial reports that play an important role in providing accounting information that serves as a credible basis for successful economic decision making. One of the causes of MSME business failure is the low quality of the financial reports produced by MSMEs. The aim of the study is to determine how to apply SAK ETAP at the Kembengan Sari Recreational Park and what impediments there are. This study is important in order to investigate the comprehension and use of SAK ETAP in SMEs. The method used in this research is qualitative. Based on the findings of this study, Kembengan Sari Recreation Park has made financial records, although it is still very basic and does not meet industry standards. This is due to a number of barriers identified in this study.